Effect of Skin Care Instructions by Nurses on Cancer Patients Receiving Cetuximab, an Anti-epidermal Growth Factor Receptor (EGFR) Antibody - Wagatsuma, Takanori; Makino, Tomoe; Imakata, Yuko; Kitayama, Yukie (Journal of Japanese Society of Cancer Nursing, 2020)
The purpose of this study is to reveal what kind of influence skin care instructions given by nurses has on skin symptoms, water content of stratum corneum ,QOL ,self care of patient who are receiving chemotherapy by Cetuximab which is an anti EGFR antibody preparation.The subjects were 10 patients with colorectal or the head and neck cancer (four patients in the control group, six in the intervention group) using the anti EGFR antibody preparation and receiving outpatient chemotherapy. we considered the patient selection shouldn’t be unbalanced in their disease and gender, The control and intervention groups were then selected in order. Skin care instructions was given based on the skin care day book the researcher made for the intervention group and evaluated them by using EQ-5D, moisture checker, and CTCAE. As a result, we could see increasing water content of stratum corneum and reduction Grade of CTCAE of a steroid user. Additionally, the improvement of the self-care ability could be seen from the interview for patients. It is suggested that the skin care intructions for patient giving anti EGFR antibody preparation is effective for their water content of stratum corneum ,skin symptom, and improvement of the self-care ability.